(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted during two consecutive seasons of 2019-2020 and 2020-2021 at Farmers’ home of Kamdebpur village of Nalchity upazila under Jhalakati district (2019-2020) and Bangladesh Agricultural Research Institute, Regional Agricultural Research Station, Rahmatpur, Barishal (2020-2021) to develop suitable protocol of chemical treatment of murta cane for improving the quality of shitalpati (cooling mat) in Bangladesh. There were nine treatments in the experiment viz., T1 = Boiled with Tamarind leaf + Cowa leaf (50g leaf/liter water), T2 = Soaking and boiled with fermented rice starch (250ml/liter water), T3 = Boiled with white vinegar (100ml/liter water), T4 = Boiled with cowa leaf + Vinegar (25g cowa leaf/liter water and 50ml vinegar/liter water), T5 = Boiled with Detergent powder (10g/liter water), T6 = Boiled with Fermented rice starch + Arrowroot (fermented rice starch 250ml/liter water and arrowroot 5g/liter water), T7 = Boiled with Tamarind leaf + Cowa leaf + Rice starch (50g leaf/liter water and fermented rice starch 250ml/liter water), T8 = Boiled with Rice starch + Fermented milk (fermented rice starch: milk = 10: 1), and T9 = Control (no treatment). The experiment was conducted in a Completely Randomized Design (CRD) with three replications. The chemical treatment had significant effect on the quantitative and qualitative traits of murta cane. In terms of qualitative traits, the lowest average value (2.58) was recorded in treatment T7 that denoted from very good to good quality of shitalpati followed by T4 treatment (rating 2.67). The rating from good to moderate qualities of shitalpati were found in T6 (3.33), closely followed by T2 (3.42) and T1 (3.42) treatment. Considering the average value of the qualitative traits (brightness, surface glossiness, surface smoothness and comfort), the treatments T7, followed by T4 and T8 could be applied for the treatment of murta cane towards weaving very good to good qualities of shitalpati. Bangladesh J. Agril. Res. 47(3): 303-308, September 2022